2014
DOI: 10.1111/1471-0528.12643
|View full text |Cite
|
Sign up to set email alerts
|

Anal incontinence and Quality of Life in late pregnancy: a cross‐sectional study

Abstract: Objective To evaluate the association between different types of anal incontinence (AI) and Quality of Life (QoL) in late pregnancy.Design Cross-sectional study.Setting Two maternity units in Norway 2009-2010.Population Primiparae aged 18 or over.Methods Participants answered questions about AI during the last 4 weeks of pregnancy on the St. Mark's score and impact of QoL in the Fecal Incontinence QoL score. Socioeconomic data were obtained from hospital records.Main outcome measures Self-reported AI and impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 37 publications
1
26
1
Order By: Relevance
“…In the present study, the focus has thus been on AI rather than FI. Previous reports have shown that women report that frequent flatus incontinence causes embarrassment and affects the quality of life more than experiencing FI alone in late pregnancy, whereas urgency alone had little effect on quality of life unless experienced in combination with other AI symptoms . Thus, urgency was included in the definition of AI only when experienced in combination with other AI symptoms and participants were categorized into one of three groups: Continent or minor AI (no FI symptoms, flatus incontinence less than weekly or urgency alone). Moderate AI (one AI symptom; FI alone monthly or more, or flatus incontinence alone weekly or more). Severe AI (combinations of two or more AI symptoms: FI monthly or more, flatus incontinence weekly or more, or urgency/inability to defer defecation for 15 min). …”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the focus has thus been on AI rather than FI. Previous reports have shown that women report that frequent flatus incontinence causes embarrassment and affects the quality of life more than experiencing FI alone in late pregnancy, whereas urgency alone had little effect on quality of life unless experienced in combination with other AI symptoms . Thus, urgency was included in the definition of AI only when experienced in combination with other AI symptoms and participants were categorized into one of three groups: Continent or minor AI (no FI symptoms, flatus incontinence less than weekly or urgency alone). Moderate AI (one AI symptom; FI alone monthly or more, or flatus incontinence alone weekly or more). Severe AI (combinations of two or more AI symptoms: FI monthly or more, flatus incontinence weekly or more, or urgency/inability to defer defecation for 15 min). …”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of any type of urinary incontinence in primiparous women during the first year postpartum, regardless of delivery mode, is between 15% and 30% 110. Johannessen et al found that one in five primiparous women suffered from anal incontinence 1 year after delivery 111. The main predictor for anal incontinence 1 year postpartum was anal incontinence in late pregnancy.…”
Section: Musculoskeletal Complaintsmentioning
confidence: 99%
“…AI affects one in four primiparous women during the third trimester 303 304. In one study, the prevalence of AI, generally limited to flatus incontinence, was higher in women (aged 18–40 years) who exercised more than 8 h/week (14.8%) than in a comparison group (4.9%, p=0.001) 305.…”
Section: Pregnancymentioning
confidence: 99%